Development of maize under influence of “pau‑branco” trees in an agrosilvopastoral system - Mendes, Marlete Moreira de Sousa; Lacerda, Claudivan Feitosa de; Cavalcante, Ana Clara Rodrigues; Fernandes, Francisco Éden Paiva; Oliveira, Teógenes Senna de (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the effect of “pau‑branco” (Cordia oncocalyx) trees on physiological parameters, height, and biomass of maize at different distances from the trees in an agrosilvipastoral system. The experimental design was a randomized complete block with four treatments (distances from trees of 1, 2, 3, and 4 m), besides a control (plants cultivated in the traditional system), and five replicates. The plots consisted of one “pau‑branco” tree at the center, and maize rows planted at the four evaluated distances from the tree stem. Physiological measurements and dry matter production were recorded at 30, 60, and 90 days after the sowing of maize. The plants under the canopy of “pau‑branco” – at 1 and 2 m from the stem – had their gas exchange, height, and dry matter production affected by the trees. The plants 3 m away from the stem had similar performance to those in the traditional system, and the plants at 4 m of distance had higher photosynthesis, stomatal conductance, transpiration, height, and dry mass production. Maize plants under the canopy are negatively affected by tree shading, whereas plants outside the canopy can be favored by the presence of trees in the system.